Determination of BLDC Motor Capacity for Electric Car Drive - Purnawan, Purnawan; Casnan, Casnan; Kurniawan, Arief; Riski, Ananda (Universitas Ahmad Dahlan, 2021)
The study's objectives were to: determine the type of Brushless Direct Current (BLDC) motor that is right for an electric car drive system with a capacity of one passenger, and Knowing the capacity of the BLDC motor used as an electric car drive system with a capacity of one passenger. This research uses Research and Development (R&D) level 1. The research subjects taken are students and lecturers of Vocational Education, Automotive Technology and Electrical Engineering, Ahmad Dahlan University, totalling eight students four lecturers. Ahmad Dahlan University